Vorapaxar and diplopia: Possible off-target PAR-receptor mismodulation - Serebruany, Victor L.; Fortmann, Seth D.; Rao, Sunil V.; Tanguay, Jean-Francois; Lordkipanidze, Marie; Hanley, Daniel F.; Can, Mehmet; Kim, Moo Hyun; Marciniak, Thomas A. (Thrombosis and Haemostasis, 2016)
Vorapaxar, a novel antiplatelet thrombin PAR-1 inhibitor, has been evaluated in the successful TRA2P trial and the failed TRACER trial. The drug is currently approved for post myocardial infarction and peripheral artery disease indications with concomitant use of clopidogrel and/or aspirin. The FDA ruled that the vorapaxar safety profile is acceptable. However, both trials revealed excess diplopia (double vision) usually reversible after vorapaxar. The diplopia risk appears to be small (about 1 extra case per 1,000 treated subjects), but real. Overall, there were 10 placebo and 34 vorapaxar diplopia cases (p=0.018) consistent for TRACER (2 vs 13 cases; p=0.010) and for TRA2P (8 vs 21 cases; p=0.018). Hence, we review the FDA-confirmed evidence and discuss potential causes and implications of such a surprising adverse association, which may be related to off-target PAR receptor mismodulation in the eye.
Keywords: Vorapaxar; PAR receptor; diplopia; adverse events; safety; clinical trials